2020
DOI: 10.1111/acv.12654
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heat acclimation capacity could leave subterranean specialists highly sensitive to climate change

Abstract: Physiological traits are key in determining the vulnerability of narrow range, highly specialized animals to climate change. It is generally predicted that species from more stable environments possess lower thermal tolerance breadths and thermal plasticity than those from more variable habitats – the so‐called ‘climatic variability hypothesis’. However, evolutionary trade‐offs between thermal breadth and its plasticity are also seen in some taxa, and the evolution of thermal physiology remains poorly understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 75 publications
3
27
0
Order By: Relevance
“…As subterranean dytiscids likely descended from only a handful of epigean lineages (Leijs et al, 2012), meaningful comparisons can be made between these taxa despite their distributions being geographically disjunct. A recent study showed that P. macrosturtensis has a reduced upper thermal tolerance (or critical thermal maximum, CT max ) of 38.3°C compared to other epigean dytiscids (42–44.5°C) (Jones et al, 2021), mirroring previous results for other cave beetle species (Pallarés et al, 2020). These results also suggest P. macrosturtensis is unlikely to reach its thermal critical maximum under current climate change predictions.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…As subterranean dytiscids likely descended from only a handful of epigean lineages (Leijs et al, 2012), meaningful comparisons can be made between these taxa despite their distributions being geographically disjunct. A recent study showed that P. macrosturtensis has a reduced upper thermal tolerance (or critical thermal maximum, CT max ) of 38.3°C compared to other epigean dytiscids (42–44.5°C) (Jones et al, 2021), mirroring previous results for other cave beetle species (Pallarés et al, 2020). These results also suggest P. macrosturtensis is unlikely to reach its thermal critical maximum under current climate change predictions.…”
Section: Introductionsupporting
confidence: 61%
“…Given the reduced thermal tolerance of P. macrosturtensis , it remains to be seen if the species could tolerate such extremes in the long term. Indeed, even cave beetles considered stenothermal–those that are only capable of surviving within an extremely narrow temperature range–have retained the HSR (Pallarés et al, 2020), but nonetheless cannot survive at extreme temperatures for long periods (>7 days) compared to epigean relatives (Bernabò et al, 2011; Rizzo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Ma (Ribera et al, 2010)) acquired morphological and physiological traits typically associated with troglobitic adaptations. Their modifications include complete lack of eyes and optic lobes, depigmentation, membranous wings, elongation of antennae and legs (Deleurance, 1963; Jeannel, 1924; Luo et al, 2019) and loss of thermal acclimation capacity (Pallarés et al, 2020; Rizzo et al, 2015). They also exhibit modified life cycles as a key innovation for their subterranean specialization (Cieslak et al, 2014; Delay, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Irreversible acclimation responses to developmental conditions might lead to maladaptive mismatches between the phenotype and ecological conditions in highly variable and unpredictable environments (Gluckman et al., 2007; Piersma & van Gils, 2011). Therefore, the ability of organisms to flexibly adjust their phenotype to environmental variations throughout their lifetime may determine their capacity to cope with climate change (Morley et al., 2019; Pallarés et al., 2020). Similarly, whether plastic responses supersede fixed inter‐individual differences in physiology has been poorly investigated so far, despite evidence of consistent physiological syndromes in some ectotherms (Goulet, Thompson, & Chapple, 2017; Mell et al., 2016).…”
Section: Introductionmentioning
confidence: 99%